2021
DOI: 10.3390/rs13245131
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Cropland Burned Area in Northeastern China by Integrating Landsat Time Series and Multi-Harmonic Model

Abstract: Accurate cropland burned area estimation is crucial for air quality modeling and cropland management. However, current global burned area products have been primarily derived from coarse spatial resolution images which cannot fulfill the spatial requirement for fire monitoring at local levels. In addition, there is an overall lack of accurate cropland straw burning identification approaches at high temporal and spatial resolution. In this study, we propose a novel algorithm to capture burned area in croplands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…While they report high errors of omission in the MODIS data, errors are likely even higher than reported due to the missing observations of CRB events in the validation set. Liu et al [58] validated a model of CRB on wheat plots in China based on a single Landsat-8 image with a single Gaofen-1 image from the same day. While their 95% accuracy can provide a good check on the ability of the model to detect recently burned plots, it says little about the ability to measure CRB overall.…”
Section: Discussionmentioning
confidence: 99%
“…While they report high errors of omission in the MODIS data, errors are likely even higher than reported due to the missing observations of CRB events in the validation set. Liu et al [58] validated a model of CRB on wheat plots in China based on a single Landsat-8 image with a single Gaofen-1 image from the same day. While their 95% accuracy can provide a good check on the ability of the model to detect recently burned plots, it says little about the ability to measure CRB overall.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of satellite remote sensing, many research scholars began to notice the efficiency of remote sensing satellite images for residue fire points monitoring [14][15][16]. These studies found that remote sensing technology can provide dynamic macro monitoring of residue fire information.…”
Section: Introductionmentioning
confidence: 99%
“…It is the most basic descriptor of forest fires [38], and accurately estimating and mapping of its area is essential for quantifying carbon budgets [39][40][41]. On the other hand, the forest burn site is the post-fire damaged area that has burned down completely [42]. It contributes to assessing the impacts and losses of fire [23,43].…”
Section: Introductionmentioning
confidence: 99%